Methodological Problems on the Way to Integrative Human Neuroscience - Kotchoubey, Boris; Tretter, Felix; Braun, Hans A.; Buchheim, Thomas; Draguhn, Andreas; Fuchs, Thomas; Hasler, Felix; Hastedt, Heiner; Hinterberger, Thilo; Northoff, Georg; Rentschler, Ingo; Schleim, Stephan; et al. (Frontiers in Integrative Neuroscience, 2016)
Neuroscience is multidisciplinary effort to understand structures and functions of the brain and brain-mind relations. This effort results in the increasing amount of data, generated by sophisticated technologies. However, these data enhance our descriptive knowledge, rather than to improve our understanding of brain functions. This is caused by methodological gaps both within and between subdisciplines constituting neuroscience, and the atomistic approach that limits the study of macro- and mesoscopic issues. Whole-brain measurement technologies do not resolve these issues, but rather aggravate them by the complexity problem. The present paper is devoted to methodological and epistemic problems that obstruct the development of human neuroscience. We neither discuss ontological questions (e.g., the nature of the mind) nor review data, except when it is necessary to demonstrate a methodological issue. As regards intradisciplinary methodological problems, we concentrate on those within neurobiology (e.g., the gap between electrical and chemical approaches to neurophysiological processes) and psychology (missing theoretical concepts). As regards interdisciplinary problems, we suggest that core disciplines of neuroscience can be integrated using systemic concepts that also entail human-environment relations. We emphasize the necessity of a meta-discussion that should entail a closer cooperation with philosophy as a discipline of systematic reflection. The atomistic reduction should be complemented by the explicit consideration of the embodiedness of the brain and the embeddedness of humans. The discussion is aimed at the development of an explicit methodology of integrative human neuroscience, which will not only link different fields and levels, but also help in understanding clinical phenomena.